2021
DOI: 10.1186/s10033-021-00543-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Rotor System with a Slant Crack Based on Fractional Damping

Abstract: The traditional modeling method of rotor system with a slant crack considers only integer-order calculus. However, the model of rotor system based on integer-order calculus can merely describe local characteristics, not historical dependent process. The occur of fractional order calculus just makes up for the deficiency in integer-order calculus. Therefore, a new dynamic model with a slant crack based on fractional damping is proposed. Here, the stiffness of rotor system with a slant crack is solved by zero st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…When the plant protection UAV is spraying, spraying system parameters, meteorological parameters, flight parameters, and other factors cause problems including droplet drift, uneven deposition distribution, and low utilization of pesticides [42,43]. To measure the quality of UAV spray, the main evaluation indicators include droplet deposition amount, droplet deposition density, droplet deposition uniformity and penetration, and droplet drift rate.…”
Section: Spraying Quality Measurement Technologymentioning
confidence: 99%
“…When the plant protection UAV is spraying, spraying system parameters, meteorological parameters, flight parameters, and other factors cause problems including droplet drift, uneven deposition distribution, and low utilization of pesticides [42,43]. To measure the quality of UAV spray, the main evaluation indicators include droplet deposition amount, droplet deposition density, droplet deposition uniformity and penetration, and droplet drift rate.…”
Section: Spraying Quality Measurement Technologymentioning
confidence: 99%
“…[ 19 ] In addition to the visual and auditory information that can be supplied by current VR and AR systems, introducing actuators and robotic systems into MR systems will offer somatosensory interaction to users, [ 20 ] further promoting their practical applications in remote‐control surgery, [ 21 ] bionic prosthesis, [ 22 ] precision aircraft control, [ 16 ] etc. Even though various devices (i.e., VR cabin, [ 23 ] helmet, [ 24 ] gloves, [ 25 ] etc.) have been created to collect the motions of users, they are unable to offer haptic feedback with sufficient interaction among human, computer, and environment.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the relationship between fractional order calculus and integer order calculus, and the properties of fractional order calculus, it can be found that the fractional order calculus integrates the effects of historical as well as nonlocal distributions and does not reflect only local and some point properties. It is this long memory property and global nature that the fractional order calculus more aptly describes; the damping properties of viscoelastic materials [22][23][24][25][26]. Coccolo et al [22] considered nonlinear Duffing oscillators in the presence of fractional damping and showed that oscillations exist in the fractional order derivatives and that their amplitude and asymptotic time change abruptly with small changes in the fractional parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Coccolo et al [22] considered nonlinear Duffing oscillators in the presence of fractional damping and showed that oscillations exist in the fractional order derivatives and that their amplitude and asymptotic time change abruptly with small changes in the fractional parameter. Li et al [23] proposed a model of oblique crack dynamics based on fractional order damping and experimentally verified that the proposed fractional order model compensates for the deficiencies of the integer order model. Zarraga et al [24] investigated the distribution of poles and the dynamic response to several excitations for different values of the parameters of the fractional damping model, and showed that the fractional model differs from the conventional viscous damping system by observing specific behaviors that cannot be replicated by the classical behavior.…”
Section: Introductionmentioning
confidence: 99%